Dead ends limit charge carrier extraction from all-polymer bulk heterojunction solar cells - Jasiūnas, Rokas; Melianas, Armantas; Xia, Yuxin; Felekidis, Nikolaos; Gulbinas, Vidmantas; Kemerink, Martijn (Advanced electronic materials, 2018)
Extraction of photocreated charge carriers from a prototypical all-polymer organic solar cell is investigated by combining transient photocurrent and time-delayed collection field experiments with numerical simulations. It is found that extraction is significantly hampered by charges getting trapped in spatial traps that are tentatively attributed to dead ends in the intermixed polymer network—in photovoltaic devices based on the same donor polymer and a fullerene acceptor this effect is much weaker. The slow-down in charge extraction leads to enhanced recombination and associated performance losses. These effects are observed in addition to the dispersive behavior that is characteristic of charge motion in energetically disordered media. Upon annealing the effects of spatial traps diminish, rationalizing the doubling in device power conversion efficiency after annealing.
Gesehen am 27.11.2019